Sodium bicarbonate supplementation and its impact on endurance performance: A PRISMA-guided systematic review - Syahrizal Islam; Muhamad Husein; Jefrio Demetrimus Nubatoni; Ulfatul Azizah Awaliyyah; Gilang Gemilang Muti; Ardan Raditya Dwi Atmaja (Journal of Applied Movement and Sport Science, 2025)
Background Sodium bicarbonate (NaHCO₃) has gained substantial attention as an ergogenic aid due to its buffering capacity, which helps mitigate exercise-induced metabolic acidosis. Its use has been widely explored in high-intensity sports where the accumulation of hydrogen ions contributes to early muscle fatigue and decreased performance. Objectives This systematic review aims to synthesize current empirical evidence regarding the effectiveness of sodium bicarbonate supplementation in enhancing endurance-related performance outcomes, with a particular focus on its role in delaying muscle fatigue during exercise. Methods A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Article identification and selection employed the PICO framework. Relevant studies were retrieved from Scopus, ScienceDirect, Web of Science, and PubMed using the keywords “sodium bicarbonate,” “endurance,” “performance,” and “muscle fatigue.” Nine peer-reviewed studies met the inclusion criteria and were analyzed descriptively to evaluate the effects of sodium bicarbonate on athletic performance. Results The findings indicate that sodium bicarbonate supplementation can enhance performance, particularly in high-intensity and short-to-medium-duration activities. However, its effectiveness is highly context-dependent and influenced by exercise modality, duration and intensity, athlete training status, and supplementation protocol—including dosage, timing, and individual physiological tolerance. Several studies employed relatively small and homogeneous samples, limiting the generalizability of the results. Conclusion Sodium bicarbonate shows consistent potential as an ergogenic supplement for improving endurance-related performance by attenuating metabolic fatigue. Nonetheless, its benefits are not uniform across all athletes or sport types. Optimal outcomes appear to require individualized dosing strategies and sport-specific application. This review provides an updated synthesis of evidence on sodium bicarbonate supplementation and highlights critical variables that moderate its effectiveness. The study underscores the need for individualized supplementation protocols and encourages future research employing larger, more diverse athlete populations and standardized ergogenic assessment methods.